2018
DOI: 10.1016/j.neuropsychologia.2018.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Beyond volume: A surface-based approach to bilingualism-induced grey matter changes

Abstract: Bilingualism is a sustained experience associated with structural changes in cortical grey matter (GM) morphology. Apart from a few studies, a dominant method used to assess bilingualism-induced GM changes has been the voxel-based morphometry (VBM) analysis. While VBM is sensitive to GM volume/density differences in general, it cannot be used to identify whether the observed difference is due to relative changes in, e.g., cortical thickness, area or folding, as it uses a single combined measure of them all. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Some evidence shows that cognitive stimulating environments lead to brain volumetric advantages and better cognitive performances. These effects are common to physiological [24][25][26] and initial pathological ageing, [27][28][29] suggesting that neuroplasticity is maintained even in diseased brains, regardless of the specific clinical picture or the underlying pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence shows that cognitive stimulating environments lead to brain volumetric advantages and better cognitive performances. These effects are common to physiological [24][25][26] and initial pathological ageing, [27][28][29] suggesting that neuroplasticity is maintained even in diseased brains, regardless of the specific clinical picture or the underlying pathological process.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was reported by Grogan, Parker Jones, Ali, Crinion, Orabona, Mechias, Ramsden, Green and Price (2012), who reported greater GM density in the right IPL for sequential multilinguals vs. bilinguals. In a different group of studies, Hämäläinen and colleagues (Hämäläinen, Joutsa, Sihvonen, Leminen & Lehtonen, 2018; Hämäläinen et al, 2017) also showed that acquiring a third language sequentially after two languages have already been acquired leads to increased GM in the left IFG and STG, and increased FA and decreased MD in the IFOF, compared to trilinguals with two sequentially acquired languages. Therefore, it appears that sequential acquisition of a third language or beyond follows a pattern of structural changes similar to those caused by sequential acquisition of a second language, suggesting that previously modulated regions need to re-adapt in order to accommodate the additional language(s).…”
Section: Brain Restructuring and Additional Language Learningmentioning
confidence: 98%
“…Indeed, the reported structural effects of bilingualism in adults (measured as differences between bilingual and monolingual groups, or sometimes in training studies) are most commonly reported in grey matter regions that have been found to underlie such language-related (as well as other) processes (for details, see Pliatsikas 2019 ). These regions primary include: frontal and nearby cortex, including the three portions of the left inferior frontal gyrus (IFG), namely, opercularis (IFGop), triangularis (IFGtr), and orbitalis (IFGor), as well as the frontal pole, the middle and superior frontal gyri (MFG and SFG), and the anterior cingulate cortex (ACC); temporal cortex, including the superior, middle, and inferior temporal gyri (STG, MTG and ITG), Heschl’s gyrus, the temporal pole, and the hippocampus; and parietal cortex, including the supramarginal gyrus, the angular gyrus, and the superior parietal lobule (Mechelli et al 2004 ; Mårtensson et al 2012 ; Abutalebi et al 2014a ; Klein et al 2014 ; Stein et al 2014 ; Kaiser et al 2015 ; Olulade et al 2016 ; Hämäläinen et al 2018 ). Subcortical structures that are affected mainly include the basal ganglia, in particular the caudate nucleus, the putamen, and the globus pallidus, as well as the thalamus (Burgaleta et al 2016 ; Pliatsikas et al 2017 ; DeLuca et al 2019a ), with some effects also having been reported in the cerebellum (Filippi et al 2011 , 2020 ; Pliatsikas et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%